Cognitive functions and patterns of brain activity in patients after simultaneous coronary and carotid artery revascularization - Tarasova, Irina; Trubnikova, Olga; Kupriyanova, Darya S.; Maleva, Olga; Syrova, Irina; Kukhareva, Irina; Sosnina, Anastasia; Tarasov, Roman; Barbarash, Olga (Frontiers in Human Neuroscience, 2023)
Background: On-pump coronary artery bypass grafting (CABG) is associated with high risk of neurological complications in patients with severe carotid stenosis. Moreover, early postoperative cognitive dysfunction (POCD) incidence remains high in patients undergoing simultaneous coronary and carotid surgery. Recent studies have shown that even moderate carotid stenosis (≥50%) is associated with postoperative cognitive decline after CABG. The data on the brain health in the postoperative period of simultaneous coronary and carotid surgery are limited. Objectives: To analyze early postoperative changes in cognitive function and patterns of brain electrical activity in patients after simultaneous coronary and carotid artery revascularization. Material and Methods: Between January 2017 and December 2020, consecutive patients were assigned to on-pump CABG with or without carotid endarterectomy (CEA) according to the clinical indications. An extended neuropsychological and electroencephalographic (EEG) assessment was performed before surgery and at 7-10 days after CABG or CABG+CEA. Results: Of one hundred patients (59.0 (55.0; 65.0), 95% male, MMSE 27.0 (26.0; 28.0), CEA was performed in 46 cases. POCD was diagnosed in 29 (63.0%) of patients with CABG+CEA, and in 32 (59.0%) of patients with isolated CABG. All patients presented with a postoperative theta power increase. However, patients with CABG+right-sided CEA demonstrated the most pronounced theta power increase compared to patients with isolated CABG. Conclusion: The findings of our study show that patients with CABG+CEA and isolated CABG have comparable POCD incidence, however, patients with CABG+right-sided CEA presented with lower brain activity.